MODEL MATEMATIKA PENYEBARAN PENYAKIT PULMONARY TUBERCULOSIS DENGAN PENGGUNAAN MASKER MEDIS - Inayah, Nur; Manaqib, Muhammad; Fitriyati, Nina; Yupinto, Ikhwal (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
This research developed a model of tuberculosis disease spread using the SIR model with addition of the medical mask usage factor. First, we create a diagram of the tuberculosis disease spread compartment through contact between individuals with medical mask usage. After that, we construct a system of nonlinear differential equations based on the compartment diagram and then find the disease-free equilibrium point, the endemic equilibrium point, and the initial reproduction number . We use linearization to analyze of the disease-free equilibrium point. The disease-free equilibrium point obtained is asymptotically stable at . The simulation result shows that the value of . It means that tuberculosis disease in the future will disappear. But if we reduce the value of medical mask usage and increase the value of tuberculosis disease spread, the value . It means that tuberculosis diseases can become an outbreak.